Characterization and antibacterial activity of cetylpyridinium bromide (CPB) immobilized on kaolinite with different CPB loadings - Nik Malek, Nik Ahmad Nizam (2015)
This paper discusses the formation of cetylpyridinium bromide (CPB), a cationic surfactant quaternary ammonium compound (QAC), immobilized on kaolinite with different initial CPB concentrations ([CPB]i) and their effect on the antibacterial activity against Escherichia coli. The CPB-immobilized kaolinites were characterized by a CHNS analyzer, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), zeta potential (ZP) analysis and the amount of CPB adsorbed on kaolinite. The antibacterial assay of the samples was studied through the disk diffusion technique (DDT) against E. coli as a model bacterium. The amount of CPB adsorbed on kaolinite did not affect the structure of the parent kaolinite but affected the overall charge of the kaolinite and eventually affected their antibacterial activity. CPB-immobilized kaolinite with [CPB]i above the critical micelle concentration (CMC) possessed antibacterial activity because of reversal of the charge from negative to positive on the kaolinite surfaces, as proven by ZP analysis, which could allow the action of CPB molecules against bacteria cells. This was due to the bilayer formation of surfactant molecules via hydrophobic bonding of their long hydrocarbon chains on the kaolinite surfaces at surfactant concentrations above the CMC value. Therefore, one of the important factors in producing antibacterial agents from surfactant immobilized kaolinite (organo-clay) is by loading excess surfactant on the clay above its CMC level to ensure bilayer formation of surfactant molecules on clay surfaces.